Prevalence of Stigma Among TB Patients and Its Associated Factors - A Community Based Cross-Sectional Study in Puducherry, India - Baskaran, Lavanya; Vasudevan, Kavita; Anandaraj (National Journal of Community Medicine, 2023)
Background: Tuberculosis (TB) is a disease that has both medical as well as social dimensions. Stigma and associated discrimination experienced by persons affected by TB is a barrier to the interventions towards TB elimination. A better understanding of stigma will improve the effectiveness of the interventions aimed to alleviate the effects of TB stigma. The objectives were to measure the prevalence of self, anticipated, experienced stigma and its associated factors and to explore the impact of tuberculosis related stigma among TB patients. Methodology: A cross-sectional study was conducted in Puducherry district, Southern India among 420 adult drug sensitive non-HIV TB patients registered under NTEP. Data was collected by face-to-face interview using standardised questionnaire. Results: The mean(±SD) age of the study participants was 44.5 (±15.03) years. Majority were males (267, 63.6%) and were married (330, 78.6%). The prevalence of stigma among TB patients was found to be 69.3%. Perceived stigma was noted in 47.1%, 33.6% had self- stigma and 26.0% had experienced stigma. On measuring the impact of stigma, 52.6% reported participation restriction. Illiteracy and lower-socio economic status were found to be significantly associated with TB stigma. Conclusions: Stigma among TB patients was high. Tailored patient-centric interventions to address stigma and discrimination using culturally appropriate and locally available resources are necessary.